Imagining Indian Nation-State: Rereading Qurratulain Hyder’s Select Novels in Contemporary Scenario - Sk Sagir Ali (SARE: Southeast Asian Review of English, 2023)
Given the contemporary hyper-nationalist ambiance in the Indian subcontinent, the reading of Qurratulain Hyder is significant, especially from the decolonial nationalist perspective of her selected translated Urdu novels. The paper examines the events and metaphors in both novels through a decolonial and transmodern lens. This approach entails establishing a relationship between history and human experience. Additionally, the paper suggests a more intricate connection between modernity and the manifold cultural aspects of the Nation-State while acknowledging the "essential ambivalence within the system of differences" as discussed by Laclau (1996, 38) as well as its impact on various disciplinary frameworks. It examines religion, culture, and ethnicity in pre-modern India as a more permeable affair with the proponent of an inclusive, tolerant Indian culture, where several nations, worldviews, and religions come together, reconcile, inter-marry, break up, and grow apart under the emergence of nationalist consciousness.